2004
DOI: 10.1136/jnnp.2003.015826
|View full text |Cite
|
Sign up to set email alerts
|

Interrater agreement of the diagnosis and classification of a first seizure in childhood. The Dutch Study of Epilepsy in Childhood

Abstract: Objective: To assess the interrater agreement of the diagnosis and the classification of a first paroxysmal event in childhood. Methods: The descriptions of 100 first paroxysmal events were submitted to two panels each consisting of three experienced paediatric neurologists. Each observer independently made a diagnosis based on clinical judgment and thereafter a diagnosis based on predefined descriptive criteria. Then, the observers discussed all patients within their panel. The agreement between the six indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 31 publications
1
21
2
Order By: Relevance
“…found in the current study are slightly lower than that reported in previous studies (Bodensteiner et al, 1988;Lanska et al, 1996;Nordli et al, 1997;Berg et al, 1999;Stroink et al, 2004). However, results from different studies cannot be easily compared because of differences in patient cohorts, type, and amount of data used, experience of the observers, and the number of categories used for classification (i.e., all studies used their own adaptation of the classification schemes to make them suitable for applying statistics).…”
Section: Study Design and Limitationscontrasting
confidence: 80%
“…found in the current study are slightly lower than that reported in previous studies (Bodensteiner et al, 1988;Lanska et al, 1996;Nordli et al, 1997;Berg et al, 1999;Stroink et al, 2004). However, results from different studies cannot be easily compared because of differences in patient cohorts, type, and amount of data used, experience of the observers, and the number of categories used for classification (i.e., all studies used their own adaptation of the classification schemes to make them suitable for applying statistics).…”
Section: Study Design and Limitationscontrasting
confidence: 80%
“…1,4,5 The generally modest interrater agreement in our study should not be surprising, as reliability has been only moderate among neurologists when independently assessing whether an event was actually a seizure, as well as the classification of the seizure. 9 Although no previous studies have evaluated interobserver agreement of clinical findings in children with unprovoked seizures when evaluated by acute care physicians (eg, ED practitioners), our results are similar to those found in the assessments of children in other clinical circumstances, and when assessments were made by neurologists. One study noted at least moderate agreement among pediatric neurologists for seizure focality ( ϭ 0.58) and seizure duration Ն10 minutes ( ϭ 0.75) in children with febrile seizures.…”
Section: Discussionsupporting
confidence: 88%
“…PNES were found in 12 children (10 girls). Their median age was 14 years (range [8][9][10][11][12][13][14][15][16][17]. Of these, only three children with concomitant epilepsy were mentally retarded.…”
Section: Resultsmentioning
confidence: 99%